2010
DOI: 10.1155/2011/379014
|View full text |Cite
|
Sign up to set email alerts
|

A Nine‐Year Audit of Open‐Access Upper Gastrointestinal Endoscopic Procedures: Results and Experience of a Single Centre

Abstract: Open-access upper gastrointestinal endoscopy is a safe and effective system. More relevant findings were found when adhering to the ASGE guidelines. However, using these guidelines as the sole determining factor in whether to perform an endoscopy is not advisable because many clinically relevant diagnoses may be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
(37 reference statements)
3
30
1
1
Order By: Relevance
“…114,115 Elsewhere in Europe, appropriateness rates for endoscopy have been reported in Portugal, Spain, Italy, and Norway, with overuse accounting for between 13% and 33% of tests, 116119 and at an Israeli center 16% of endoscopies were unnecessary. 120 Studies in the US have reported overuse rates as high as 60% 121 . In Saudi Arabia, which has open access to endoscopy, nearly half of procedures were inappropriate.…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…114,115 Elsewhere in Europe, appropriateness rates for endoscopy have been reported in Portugal, Spain, Italy, and Norway, with overuse accounting for between 13% and 33% of tests, 116119 and at an Israeli center 16% of endoscopies were unnecessary. 120 Studies in the US have reported overuse rates as high as 60% 121 . In Saudi Arabia, which has open access to endoscopy, nearly half of procedures were inappropriate.…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…[15][16][17] Literature suggests that this has resulted in an increase in a number of unnecessary procedures which range from 5 to 49%. 19 Similarly they also found 440 (2.13%) gastric malignancies out of which 392 (1.90%) had appropriate indication and 48 (0.23%) had inappropriate indications. 19 The difference from our findings with this large study may be due to small sample size in our study.…”
Section: Discussionmentioning
confidence: 86%
“…19 Similarly they also found 440 (2.13%) gastric malignancies out of which 392 (1.90%) had appropriate indication and 48 (0.23%) had inappropriate indications. 19 The difference from our findings with this large study may be due to small sample size in our study. Hence, guidelines should be used cautiously in order not to miss important diagnosis and the clinical suspician and clinical judgements should always come before the guidelines.…”
Section: Discussionmentioning
confidence: 86%
“…We collapsed the diagnosis field into nine different binary (present/absent) covariate fields: achalasia, Barrett’s oesophagus, diverticulum, extrinsic compression, malignancy, peptic ulcer disease, polyps, varices and other diagnoses. Previous publications have classified OGD diagnoses into 1818 or 21 categories 19. We chose nine categories as these could be grouped easily from the diagnosis field options in the JETS database and the overall number of categories was minimised to simplify the multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%